Paleotsunami evidence on Kaua'i and numerical modeling of a great Aleutian tsunami. Issue 19 (3rd October 2014) - Butler, Rhett; Burney, David; Walsh, David
<x xml:space="preserve">Abstract</x> The Hawaiian Islands' location in the middle of the Pacific Ocean is threatened by tsunamis from great earthquakes in nearly all directions. Historical great earthquakes Mw > 8.5 in the last 100 years have produced large inundations and loss of life in the islands but cannot account for a substantial (≤ 600 m3) paleotsunami deposit in the Makauwahi sinkhole on the Island of Kaua'i. Using high‐resolution bathymetry and topography we model tsunami inundation of the sinkhole caused by an earthquake with a moment magnitude of Mw ~9.25 located in the eastern Aleutians. A preponderance of evidence indicates that a giant earthquake in the eastern Aleutian Islands circa 1425–1665 A.D.—located between the source regions of the 1946 and 1957 great tsunamigenic earthquakes—created the paleotsunami deposit in Kaua'i. A tsunami deposit in the Aleutians dated circa 1530–1660 A.D. is consistent with this eastern Aleutian source region.